Effect of Nursing Model Based on Rosenthal Effect on Self-Efficacy and Cognition of Life Meaning in Patients with Non-Small-Cell Lung Cancer. (8th August 2022) - Mao, Linghua; Lu, Huaqin; Lu, Yangyang
Abstract : Objective . To study the influence of nursing model based on Rosenthal effect on self-efficacy and cognition of life meaning in patients with non-small-cell lung cancer (NSCLC). Methods . 120 patients with NSCLC treated in the hospital were selected from November 2020 to November 2021 and were randomly divided into the nursing group and the Rosenthal group, with 60 cases in each group. The nursing group received routine nursing intervention, while the Rosenthal group was intervened by nursing model based on the Rosenthal effect, and both groups were intervened for 1 month. The self-efficacy (General Self-Efficacy Scale (GSES)), negative emotions (Hospital Anxiety and Depression Scale (HADS)), self-burden (Self-Perceived Burden Scale for Cancer Patients (SPBS-CP)), meaning of life (Meaning of Life Scale for Advanced Cancer Patients (MiLS)), and quality of life (Functional Assessment of Cancer Therapy-Lung (FACT-L)) were compared between the two groups before and after intervention. Results . After 1 month of intervention, the scores of GSES and MiLS of patients in the two groups were significantly higher than those before intervention, and the scores in the Rosenthal group were significantly higher than those in the nursing group (P < 0.05 ). The scores of HADS, SPBS-CP, and FACT-L in the two groups were significantly lower than those before intervention, and the scores were significantly lower in the Rosenthal group than those in the nursing group (P < 0.05 ). Conclusion . Nursing model intervention based on Rosenthal effect enhances the self-efficacy and meaning of life and reduces the negative emotions and self-burden in patients with NSCLC.